Growth and leaf epidermal response of three Sesamum indicum varieties to industrial effluent irrigation - Rahaman, AA Abdul; Olaniran, OM; Oladele, FA (Bangladesh Journal of Scientific and Industrial Research, 2017)
The effect of industrial effluents was studied with respect to growth and leaf anatomy of three Sesamum indicum varieties (NGB 00931, NGB 00937 and NGB 00939). Industrial effluents (25%, 50%, 75% and 100%) from two industries are used to irrigate the plants. Although, the control plants possessed larger leaves and longer stems than the effluent-treated plants, at lower concentration, the plant growth is relatively higher. Gradual decrease in the germination of seeds and seedling growth with increase in effluent concentration was observed. The best germination and seedling growth was observed at the 25% concentration. Leaf epidermal features (stomatal density, stomatal index, stomatal size, trichome density, tricome index, trichome size and number of epidermal cells) are more influenced in the effluent-treated plants than in the control plants from the Peace Standard Pharmaceutical Industry than in the effluent from the Global Soap & Detergent Industry. Thus the industrial effluents can be safely used for irrigation purposes with proper treatment and dilution at 25%. Bangladesh J. Sci. Ind. Res. 52(1), 1-6, 2017